2006
DOI: 10.1111/j.1526-4610.2006.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Not Tonight, I Have a Headache?

Abstract: Migraine headaches and sexual desire both appear to be at least partially modulated by serotonin (5-HT). The metabolism of 5-HT has been shown to covary with the onset of a migraine attack, and migraineurs appear to have chronically low systemic 5-HT. As sexual desire also has been linked to serotonin levels, the results are consistent with the hypothesis that migraine and sexual desire both may be modulated by similar serotonergic phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
(45 reference statements)
2
19
2
2
Order By: Relevance
“…Some earlier studies compared migraine patients with healthy controls, 8,9 and one study compared migraine patients with tension-type headache patients. 18 Our results suggest that people suffering from headaches experience dysfunction in all domains of sexuality relative to those who are healthy.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Some earlier studies compared migraine patients with healthy controls, 8,9 and one study compared migraine patients with tension-type headache patients. 18 Our results suggest that people suffering from headaches experience dysfunction in all domains of sexuality relative to those who are healthy.…”
Section: Discussionmentioning
confidence: 67%
“…In a study, they conducted relying on the assumption that migraines and sex drive could be modified by similar serotonergic systems, Houle et al 18 found that those who suffered from migraines reported a higher sex drive than those suffering from tension-type headaches. In our study, we did not use a specific scale to evaluate sex drive, such as the Sexual Desire Inventory, 19 whereas Houle et al 18 did; and this might account for our failure to detect any such difference. In further studies, it would be advantageous to assess sex drive in different subgroups of headache patient using a more detailed survey instrument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that chronic illnesses are related to sexual dysfunction [1], migraine as a chronic condition mainly seen in women is known to negatively affect quality of life [2] as well as sexual function [3-6]. Several studies have investigated the relationship between headache and sexual function.…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that both patient groups with tension type headache and migraine had high levels of anxiety and depression, but that depression did not show a positive correlation with sexual distress in migraineurs. On the other hand, some authors have suggested that migraine sufferers have higher levels of sexual desire than those suffering from tension type headache [6]. …”
Section: Introductionmentioning
confidence: 99%